A Statistical Approach to Analyze the Impact of Random Discrete Dopant (RDD) and Oxide Thickness Variation (OTV) on the Performance of a Low Power Folded Cascode OTA - Dutta, Tanusree; Sarkhel, Saheli; Banerjee, Soham; Pandit, Soumya (Devices for Integrated Circuit, 2025)
The proposed work endeavours to present a statistical study to determine the nature of variation of the major performance parameter i.e. voltage gain of a low power Folded Cascode Operational Transconductance Amplifier (OTA) subject to variations of the two major process parameters-threshold voltage (V th ) and gate oxide thickness (t ox ). The process parameter variations are considered to follow a normal distribution about a mean value with a 3% standard deviation. The OTA circuit is simulated in Spice environment using Python script to generate the entire data set for V th and t ox variations. The OTA gain from the generated data set is analyzed statistically using R programming to determine its nature of variation and is compared with three standard distributions: normal, lognormal and Weibull. The study reveals that the nature of variation of OTA gain due to V th variation follows a normal distribution where OTA gain due to t ox variation follows a Weibull distribution.